Residue-based propensity of aggregation in the Tau amyloidogenic hexapeptides AcPHF6*and AcPHF6 - Dangi, Abha; Balmik, Abhishek Ankur; Ghorpade, Archana Kisan; Gorantla, Nalini Vijay; Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose; Marelli, Udaya Kiran (RSC Advances, 2020)
In Alzheimer's disease and related tauopathies, the aggregation of microtubule-associated protein, Tau, into fibrils occursviathe interaction of two hexapeptide motifs PHF*(275)VQIINK(280)and PHF(306)VQIVYK(311)as beta-sheets. To understand the role of the constituent amino acids of PHF and PHF* in the aggregation, a set of 12 alanine mutant peptides was synthesized by replacing each amino acid in PHF and PHF* with alanine and they were characterized by nuclear magnetic resonance (NMR) spectroscopy, circular dichroism (CD), transmission electron microscopy (TEM) and ThS/ANS fluorescence assay. Our studies show that while the aggregation was suppressed in most of the alanine mutant peptides, replacement of glutamine by alanine in both PHF and PHF* enhanced the fibrillization.